2019
DOI: 10.1002/jcb.29317
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed circular RNAs in maternal and neonatal umbilical cord plasma from SGA compared with AGA

Abstract: Small for gestational age (SGA) has a high risk of mortality and morbidity and is common in obstetrics. To date, no effective prediction and treatment tools are available. Acting as microRNA (miRNA) sponges and disease biomarkers are clear functions of circular RNAs (circRNAs). However, it is still unknown what role circRNAs act in SGA. To explore the role of circRNAs in SGA, circRNA expression patterns of the umbilical cord and maternal plasma in SGA was assessed. We first evaluated circRNAs in umbilical cord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Unfortunately, the biological roles of hsa_circ_0001360 are currently very little studied. Only a recent study [33] reported that hsa_circ_0001360 was markedly down‐regulated in the placental tissue and plasma of small‐for‐gestational‐age fetuses compared with appropriate‐for‐gestational‐age fetuses and had two target miRNAs (hsa_miR_4725_3p and hsa_miR_671_5p) that were significantly elevated in placental tissue of small‐for‐gestational‐age fetuses. Interestingly, hsa_miR_4725_3p was observed to be up‐regulated in patients with glaucoma [34] and was involved in xanthohumol‐attenuated glioma cell invasion [35] and cotreatment of melatonin‐ and pterostilbene‐induced apoptosis of colorectal cancer cells [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the biological roles of hsa_circ_0001360 are currently very little studied. Only a recent study [33] reported that hsa_circ_0001360 was markedly down‐regulated in the placental tissue and plasma of small‐for‐gestational‐age fetuses compared with appropriate‐for‐gestational‐age fetuses and had two target miRNAs (hsa_miR_4725_3p and hsa_miR_671_5p) that were significantly elevated in placental tissue of small‐for‐gestational‐age fetuses. Interestingly, hsa_miR_4725_3p was observed to be up‐regulated in patients with glaucoma [34] and was involved in xanthohumol‐attenuated glioma cell invasion [35] and cotreatment of melatonin‐ and pterostilbene‐induced apoptosis of colorectal cancer cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…In additional, Verduci et al [32] reported that the Unfortunately, the biological roles of hsa_circ_0001360 are currently very little studied. Only a recent study [33] reported that hsa_circ_0001360 were markedly downregulated in the placental tissue and plasma of small for gestational age (SGA) fetuses compared to appropriate for gestational age fetuses, and had two target miRNAs (hsa_miR_4725_3p and hsa_miR_671_5p) that were significantly elevated in placental tissue of SGA fetuses. Interestingly, hsa_miR_4725_3p was observed to be upregulated in patients with glaucoma [34], and was involved in…”
Section: Prediction Of Circrna-mirna-mrna Interaction Network Of Hsa_mentioning
confidence: 99%
“…Upregulated hsa_circ_0089172 expression was confirmed using RT-qPCR, whilst in vitro experiments revealed that hsa_circ_0089172 could be a potential diagnostic biomarker, as it plays a crucial role in the pathogenesis of Hashimoto's thyroiditis by sponging miR-125a-3p. Zhao et al ( 37 ), Qian et al ( 38 ) and Wang et al ( 39 ) assessed differences in the circRNA expression level of peripheral blood samples from patients with community-acquired pneumonia, active pulmonary tuberculosis, and in patients who were small for their gestational age, respectively, with their results suggesting that circRNAs could be reliable biomarkers for diagnosing these conditions. Notably, to the best of our knowledge, the effects of aberrant circRNA expression on ISS has not been investigated, even though an increasing number of studies have investigated the functions of circRNAs in diseases ( 34 - 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs have a clear function of acting as miRNA sponges [23]. The cCDR1as/miR-7 signal axis has been investigated in many diseases [24,25,26].…”
Section: Discussionmentioning
confidence: 99%